Application of Acrylates in Enhanced Oil Recovery - El-hoshoudy, A.N.; Desouky, S.M.; Gomaa, S. (Journal of New Developments in Chemistry, 2019)
Currently, enhanced oil recovery (EOR) acquire increased attention to recover more residual oil trapped after the primary and secondary process in petroleum reservoirs. EOR comprise different technologies involving chemical, thermal, miscible flooding techniques. Chemical flooding by the polymer is a widely implemented method on the academic and industrial scale. In this chapter, the authors discuss polymer flooding using polyacrylates that involve hydrolyzed polyacrylamide (HPAM), hydrophobically associated polyacrylamides (HAPAM), which grafted with different vinyl monomers such as acrylic acid, methyl methacrylates, and 2-acrylamido-2-methylpropane sulfonic acid (AMPS). These polymers increase the viscosity of injected brine solutions, as a result, decrease mobility ratio and enhance sweeping efficiency, so the water act as a piston, which pushes oil in front of it, and consequently increase the recovery factor. The advantages and disadvantages of these polymers as well as comparing different flooding scenarios are reported.
Keywords: Acrylates; enhanced oil recovery; polymer flooding